Boop: Acrylic on Canvas, 11"x14", 2025 - Gutierrez, Veronica (Northridge Review, 2025)
This little... well, now big kitty has played such an important role in my growing up. She has been by me through thick and thin. Nothing feels better than to make up to her booping my nose with hers! While it may seem silly, I wanted to memorialize her while I still have this 16-year-old baby with me. She really is my best friend and I will boop her at every chance I get!